ANALISIS KESULITAN BELAJAR MATEMATIKA PADA TOPIK LOGIKA DI SMK MUHAMMADIYAH 3 KLATEN UTARA - Aji Permana Putra (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Mathematics is the basis of all sciences, one that is emphasized in learning mathematics is logic thinking. In learning in vocational mathematics mathematics is an important material because logic underlies mathematical thinking, in fact there are still many students who have difficulty in learning mathematical logic material, so it needs to be analyzed to find out the learning difficulties of students in learning mathematics especially mathematics topics. In addition, the causative factors of learning difficulties in mathematics also need to be analyzed in terms of physiological, social, emotional, intellectual and pedagogical factors, so that the right solution to overcome mathematical learning difficulties, especially the topic of mathematical logic.